Decomposition of the black-white wage differential in the physician market - Tsu-Yu Tsao; Andrew Pearlman (Levy Economics Institute of Bard College, 2010)
This paper proposes a difference-in-differences strategy to decompose the contributions of various types of discrimination to the black-white wage differential. The proposed estimation strategy is implemented using data from the Young Physicians Survey. The results suggest that potential discrimination plays a small role in the racial wage gap among physicians. At most, discrimination lowers the hourly wages of black physicians by 3.3 percent. Decomposition shows that consumer discrimination accounts for all of the potential discrimination in the physician market, and that the effect of firm discrimination may actually favor black physicians. Interpretations of the estimates, however, are complicated by the possibility that, relative to white physicians, black physicians negatively self-select into self-employment.
Keywords: J01; J7; J44; 330; discrimination; physician market; wage gaps